2010
DOI: 10.1007/s11244-010-9593-6
|View full text |Cite
|
Sign up to set email alerts
|

Microcalorimetric and FTIR Study of the Adsorption of Carbon Dioxide on Alkali-Metal Exchanged FER Zeolites

Abstract: Adsorption of CO 2 on alkali-metal exchanged (Li ? , Na ? , K ? ) FER zeolites was investigated by means of microcalorimetry and FTIR spectroscopy. The adsorption enthalpies strongly depend on coverage for all investigated materials and they are also influenced by concentration of Al in the framework. Especially, samples of Na-and K-FER with lower Si/Al ratio (8.6) exhibited substantially larger initial interaction energy than samples with Si/Al 27.5. Differences in zero-coverage adsorption energy of zeolites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…A physisorbed molecule, however, was observed, as confirmed by peaks at 2348 and 2346 cm -1 for H-β and H-FER, respectively, which intensified when the temperature was decreased [211]. Other authors analyzed alkali ion-exchanged H-FER zeolites, too, and also did not detect any formation of carbonates, when CO 2 molecules were adsorbed [213]. For Na + and K + , exchanged surface peaks at 2370 and 2357 cm -1 were observed due to the physisorbed CO 2 species.…”
Section: Co 2 Adsorption On Metal Oxide Surfaces In the Presence Of Cmentioning
confidence: 93%
“…A physisorbed molecule, however, was observed, as confirmed by peaks at 2348 and 2346 cm -1 for H-β and H-FER, respectively, which intensified when the temperature was decreased [211]. Other authors analyzed alkali ion-exchanged H-FER zeolites, too, and also did not detect any formation of carbonates, when CO 2 molecules were adsorbed [213]. For Na + and K + , exchanged surface peaks at 2370 and 2357 cm -1 were observed due to the physisorbed CO 2 species.…”
Section: Co 2 Adsorption On Metal Oxide Surfaces In the Presence Of Cmentioning
confidence: 93%
“…The adsorption and separation of CO 2 from gas streams is an important area of research, and there are many published works, both experimental and computational, on adsorption and diffusion in bulk zeolite structures [28][29][30][31][32][33][34][35][36][37][38][39][40] using a variety of potential models. [41][42][43][44] Surface effects are very important for adsorption and much less work has been carried out on the adsorption and transport of CO 2 at zeolite surfaces, so this is where we chose to focus our work.…”
Section: Co 2 Adsorption In Zeolitesmentioning
confidence: 99%
“…Adsorption performance of the zeolites was usually interpreted on the basis of the idea of extra-framework cations as specific and isolated adsorption centers. However, combined experimental and theoretical studies carried out in past decade showed that even small molecules such as CO [6][7][8][9][10][11][12][13][14][15][16] or CO2 [17][18][19][20] could interact with more than only one extra-framework cation due to existence of confined space in zeolite channels and cavities and specific spatial distribution of the cations within this confined space. [21] Molecules bridging nearby cations in so called dual-cation sites (or even multiple-cation sites) were characterized by specific shifts of vibrational frequencies of bonds in the adsorbed molecules, and a stronger interaction with the zeolite than complexes formed on isolated extra-framework cations (so called single-cation sites).…”
Section: Introductionmentioning
confidence: 99%